(untitled) (Medical Forum Monthly, 2021)
Objective: To study the frequency of metabolic syndrome in patients with systemic lupus erythematosus. Study Design: Quasi-Experimental Study. Place and Duration of Study: This study was conducted at the Rheumatology Department, Shaikh Zayed Hospital Lahore from October 2017 to October 2018. Materials and Methods: Two hundred and forty patients who fulfilled the study protocol and consented were enrolled for this study. Enrolled patients were grouped into 2 categories. Group-A SLE movement record and Group-B: Controls. Serum samples for sugar, lipid profile including to talcholesterol, high-thickness lipoprotein (HDL), low-thickness lipoprotein (LDL), triglycerides, andInsulin (pg/ml). Categorical data was analyzed using Chi-square Test using (SPSS) v 23. A p-value ≤0.05 was taken as significant. Results: In Group A, 25 (20.8%) were males and 95 (79.2%) females, while in Group-B 15 (12.5%) were males and 105 (87.5%) females. Mean age of the patients in group-A was 40.2±11.7 years, while 36.6±11.6 years in group-B. While comparing the Metabolic syndrome (MetS) in both groups, MetS was noted in 35 (29.2%) patients in Group-A and 18 (15.0%) in Group-B Conclusion: Systemic lupus erythematosus with patients have higher prevalence of metabolic syndrome than controls. Syndrome was associated with higher level of inflammation and provide inflammation and increased cardiovascular risk.